Facile Preparation of High-Performance Polythiophene Derivative and Effect of Torsion Angle Between Thiophene Rings on Electrochromic Color Change - Qingfu Guo; Chao Sun; Yiran Li; Kaoxue Li; Xishi Tai (Molecules)
The electrochromic phenomenon of conducting polymer is mainly dominated by the π-π* band transition. The π conjugation is influenced by the coplanarity between polymer units, deviations from which can lead to an increased ionization potential and band gap values. In order to investigate the effect of plane distortion angle on electrochromic color in the main chain structure of polymerization, high-performance poly(3,3′-dimethyl-2,2′-bithiophene) (PDMeBTh) with a large plane distortion angle is successfully synthesized in boron trifluoride diethyl etherate (BFEE) by the electrochemical anodic oxidation method. The electrochemical and thermal properties of PDMeBTh prepared from BFEE and ACN/TBATFB are compared. The electrochromic properties of PDMeBTh are systematically investigated. The PDMeBTh shows a different color change (orange-yellow in the neutral state) compared to poly (3-methylthiophene) (light-red in the neutral state) due to the large torsion angle between thiophene rings of the main polymer chain. The optical contrast, response time, and coloring efficiency (CE) of the prepared PDMeBTh are also studied, which shows good electrochromic properties. For practical applications, an electrochromic device is fabricated by the PDMeBTh and PEDOT. The color of the device can be reversibly changed between orange-yellow and dark blue. The light contrast of the device is 27% at 433 nm and 61% at 634 nm. The CE value of the device is 403 cm2 C−1 at 433 nm and 577 cm2 C−1 at 634 nm. The constructed device also has good open circuit memory and electrochromic stability, showing good potential for practical applications.